1993
DOI: 10.3109/13813459308998134
|View full text |Cite
|
Sign up to set email alerts
|

Variation of gastric lipase secretion in the Heidenhain pouch of the cat

Abstract: In the cat, gastric lipase secretion was equally but weakly stimulated by pentagastrin, a major stimulant of acid secretion, and by carbamylcholine, a major stimulant of pepsin secretion. Lipase was also stimulated by fresh liver, which induces a large blood gastrin release and not by canned food, which is a poor gastrin releaser. Lipase output always preceded that of acid an pepsin. Lipase was not correlated with acid and pepsin secretion while acid and pepsin were well correlated during all stimulations but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Using specific polyclonal antibodies to human gastric lipase (HGL) and fundic pepsinogen (Pg5), the same group focused their efforts on establishing the cellular origin of both digestive enzymes in the human stomach. These results indicated that HGL is always colocalized with Pg5 in chief cells of the fundic mucosa (Moreau et al, 1989) and never in mucus-type nor cells in the upper part of the gland as previously reported in dog (Carrière et al, 1992), cat (Descroix-Vagne et al, 1993), and rabbit (Moreau et al, 1990) gastric biopsies. These important findings established the existence of a unique feature for the human adult gastric mucosa regarding the cellular distribution of pepsinogen (Pg5) and gastric lipase (HGL).…”
Section: Tissular Origin and Cellular Distribution Of Gastric Digestisupporting
confidence: 66%
See 1 more Smart Citation
“…Using specific polyclonal antibodies to human gastric lipase (HGL) and fundic pepsinogen (Pg5), the same group focused their efforts on establishing the cellular origin of both digestive enzymes in the human stomach. These results indicated that HGL is always colocalized with Pg5 in chief cells of the fundic mucosa (Moreau et al, 1989) and never in mucus-type nor cells in the upper part of the gland as previously reported in dog (Carrière et al, 1992), cat (Descroix-Vagne et al, 1993), and rabbit (Moreau et al, 1990) gastric biopsies. These important findings established the existence of a unique feature for the human adult gastric mucosa regarding the cellular distribution of pepsinogen (Pg5) and gastric lipase (HGL).…”
Section: Tissular Origin and Cellular Distribution Of Gastric Digestisupporting
confidence: 66%
“…Indeed, studies performed with dog and cat models revealed the presence of pepsinogen in chief cells located at the bottom of the fundic glands (Carrière et al, 1992;Descroix-Vagne et al, 1993), whereas gastric lipase was localized to mucoustype cells of the pit compartment in both species. Of note, in the fundic mucosa, no colocalization of pepsinogen and gastric lipase was reported.…”
Section: Tissular Origin and Cellular Distribution Of Gastric Digestimentioning
confidence: 99%
“…In humans, this function is assumed by the existence of a gastric lipase (HGL) co-localized with pepsinogen-5 (Pg5) in secretory granules [Moreau et al, 1988]. This co-localization is a unique feature of human gastric chief cells since both zymogens are either expressed in different gastric cell types [Carrie Áre et al, 1992;Descroix-Vagne et al, 1993] or distinct zymogenic cell populations [Bernadac et al, 1991] in animal models. Gastric triglyceride digestion is a prerequisite for optimal intestinal lipolysis [Carrie Áre et al, 1993].…”
mentioning
confidence: 99%
“…This suggests that consuming milk fat releases gastric lipase. Secretion of this enzyme can also be stimulated in adult animals including the cat if fed a diet extremely high in fat for at least 2 weeks (Bore1 et al, 1991;Descroix-Vagne et al, 1993). Weaned and adult animals examined in our study were fed canned food, which is known to Fig.…”
Section: Discussionmentioning
confidence: 83%
“…In a study on the effect of pharmacological releasers of lipase (pentagastrin and carbamylcholin) in adult cats, in accordance with our results, gastric lipase was localized in the surface mucous cells. However, in adult cats enzyme activity additionally can be found in the gastric chief cells (Descroix-Vagne et al, 1993). The reason for this is not known but can be speculated in a development-specific variation of lipase production.…”
Section: X80mentioning
confidence: 98%